Resolution of Consumer Disputes for Compensation Through Compliment Night Reviewed From Economic Analysis Of Law Theory - Wahyuni, Sri; Fakhriyah, Efa Laela; Afriana, Anita; Retnaningsih, Sonyendah (Journal of Ecohumanism, 2024)
When there is an agreement between the consumer and the business actor regarding participation as a member, the agreement that has been made together creates rights and obligations for each party and must be implemented in good faith. As agreed, the business actor has the right to receive a certain amount of payment and is obliged to provide member facilities such as accommodation, spa, gym and other services as agreed. On the other hand, the consumer has paid a certain amount of money as a member but has not received one of his rights, namely a complimentary night (lodging) for two nights at the hotel. Consumers have asked for their rights several times but business actors have not been able to fulfill them. The question arises, how to resolve disputes regarding compensation for consumer compliment night rights in terms of economic analysis of law theory? This case was resolved through court. The research method in this research uses a normative legal research method with a case approach. This research uses the theory of Economic Analysis of Law. The results of this research are to determine the resolution of compensation disputes regarding consumer rights in terms of economic analysis of law theory.